DISPUTES IN THE SECOND MARRIAGE WITHOUT THE PERMISSION WIFEFIRST - Fathimah Shalehah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2022)
Marriage according to Law Number 1 of 1974 concerning Marriage is an inner and outer bond between a man and a woman to form a happy household. The authority of polygamy is not absolute in the hands of the husband, but there are other conditions that must be met, namely getting permission from the judge (court). The purpose of this study is to analyze the regulation of criminal sanctions in a second marriage without the permission of the first wife and the legal consequences of a second marriage that does not meet the applicable legal provisions. This study uses a normative legal research method with an approach to legislation. Sources of legal materials used are primary and secondary sources of legal materials. Data collection techniques were carried out by examining existing library materials which were then analyzed systematically. The results of the study reveal that criminal sanctions are given in the second marriage without providing incorrect information based on the criminal provisions in PP No. 9 of 1975 which is a lex specialis of the Criminal Code. The legal consequence of the second marriage is that if the husband has remarried or has polygamy without the knowledge of the first wife, the first wife can sue by submitting a request for annulment of the marriage contained in Articles 22-29 of the Marriage Law